“It’s not the whole truth”. The notions of truth and falsehood as persuasive devices in Polish and Swedish parliamentary talk - Domeradzka, Magdalena (Folia Scandinavica Posnaniensia, 2019)
The article analyses references made to the notion of truth and falsehood in Swedish and Polish parliamentary talk. The results show that despite the mainstreaming of post-structuralism in contemporary society, the notion of truth – the central question of Western philosophy – is still present the parliamentary talk and in the ways in which MPs deliberate and engage in arguments. As the article argues, the MPs deploy discursive strategies exploiting mostly the classical or early modern objective theories of truth. Seeing truth as the ultimate value makes it expedient as a persuasive device and part of epideictic oratory. Apart from the similarities found in the Swedish and Polish parliamentary talk, the article shows differences mainly in how directly an accusation of lying can be voiced in the two parliaments.